Genetic Diversity and Structure of a Diverse Population of Picea sitchensis Using Genotyping-by-Sequencing - Tomás Byrne; Niall Farrelly; Colin Kelleher; Trevor R. Hodkinson; Stephen L. Byrne; Susanne Barth (Forests, 2022)
Picea sitchensis, Sitka spruce, is of interest to forestry as both a conservation species and a highly productive crop. Its native range stretches from Alaska to California, and it is hence distributed across a large environmental cline with areas of local adaptation. The IUFRO collection, established in 1968–1970, consists of 81 provenances of commercial and scientific interest spanning this native range. We used genotyping-by-sequencing on 1177 genotypes, originating from 80 of the IUFRO provenances which occupy 19 geographic regions of the Pacific Northwest, resulting in an SNP database of 36,567 markers. We detected low levels of genetic differentiation across this broad environmental cline, in agreement with other studies. However, we discovered island effects on geographically distant populations, such as those on Haida Gwaii and Kodiak Island. Using glaciation data, alongside this database, we see apparent post-glacial recolonization of the mainland from islands and the south of the range. Genotyping the IUFRO population expands upon the use of the collection in three ways: (i) providing information to breeders on genetic diversity which can be implemented into breeding programs, optimizing genetic gain for important traits; (ii) serving a scientific resource for studying spruce species; and (iii) utilizing provenances in breeding programs which are more tolerant to climate change.